The study of headspace sampling for the measurement of Volatile Organic Compounds byGC-MS - Hovánszki, Dóra; Prokisch, József; Győri, Zoltán (Acta Agraria Debreceniensis, 2006)
Headspace sampling was studied for GC-MS measurements. A quick, direct method was developed for the measurement of petrol, gasoline and volatile organic solvent contamination of soil. According to our results this method is suitable for quick qualitative analysis of VOC contamination of soil, and helps to make decisions about further measurements. We concluded that an accurate quantitative measurement is not possible.